Air-layering of Trees with Differential Adventitious Rooting Response - Singh, Sanjay; Kumar, Pramod; Mandal, A. K.; Ansari, S. A. (Indian Forester, 2004)
Five economically important forestry species namely Anogiessus latifolia, Boswellia serrata, Dalbergia latifolia, Dalbergia sissoo and Gmelina arborea having differential adventitious rooting response were evaluated for air-layering. Shoots of randomly selected trees of each species were girdled and covered with soilrite and black polythene. After forty five days, the air-layered shoots were detached from the trees to record observations on alive air-layered shoot (%), callusing (%), rooting (%), root number, root length, root fresh and dry weight. The procedure was found to be feasible for clonal propagation of Boswellia serrata and Dalbergia sissoo with 52 % and 68 % adventitious rhizogenesis, respectively. Formation of callus in Dalbergia latifolia, Anogiessus latifolia and Gmelina arborea suggests strong possibility of successful air. layering if suitable exogenous treatments are provided.